Simulação numérica de pilares danificados e recuperados com fibras de carbono usando o CDP - Nunes, Savina Laís Silva (2021)
Studies have currently increased about evaluating the application of carbon fiber reinforced polymers (CFRP) in the confinement of degraded reinforced concrete pillars. CFRP is a material that has stood out in the recovery of these pillars, even when they are made with high-performance concrete. This material has excellent mechanical properties and low specific weight, which justifies its increasing use. In this context, performing a structural evaluation is essential, whether through laboratory tests or computational modeling. Several numerical methods can be used, especially the Finite Element Method. The main objective of this work is to discuss the modeling of damaged reinforced concrete columns subjected to a concentric axial load jacketed with carbon fibers. This work is divided into two steps. In the first, reinforced concrete columns reinforced with CFRP, without damage, subjected to eccentric load, are analyzed. In these cases, the carbon fiber is modeled with shell elements considering them as isotropic, orthotropic, or lamina, and its cross-section is deemed to be composite or homogeneous. In the second step, columns with damaged high-performance concrete are analyzed, submitted to concentric axial load, and recovered with grout and CFRP, using the fiber modeling that provided better results in the first stage. The analyzes were performed using the ABAQUS® software, whose non-linearity of the concrete is modeled through the constitutive model Concrete Damage Plasticity (CDP). All simulated models were compared with experimental results extracted from the literature. Thus, it can be observed that the use of the orthotropic shell elements provides results much closer to those of reference, and the section configured as composite is the one that provides the best results. From the analysis of the damaged and recovered columns, it is possible to verify the reach of good results of peak load resistance recovery.